PERLINDUNGAN KONSUMEN TERHADAP IKLAN YANG MENYESATKAN PADA BROSUR IKLAN PERUMAHAN DIKAITKAN DENGAN PRINSIP TANGGUNG JAWAB MUTLAK (STRICT LIABILITY) - Muhammad Valgunadi; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In the Procedure of advertising in Indonesia there is a principle or general principle that the advertisement must be honest, responsible and not contrary to applicable law. However, at this time ads circulating in the community tend to have an agitating element and lie elements that are very detrimental to consumers, the problem is regulated in Law No. 8 of 1999 on Consumer Protection. Therefore, the purpose of writing this thesis, namely: First, to know the consumer protection against misleading advertising on brochure housing ads associated with the principle of absolute liability (strict liability). Second, to know the cause of the existence of ads that mislead consumers on the housing ad brochure. This type of research can be classified in the type of empirical or sociological law research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Pekanbaru City. Sources of data used, namely: primary data and secondary data. Data collection techniques in this study with Observation, Interview, and Library Studies. Conclusions can be obtained from the results of the study First, Consumer protection against advertising that is not in accordance with the goods offered, such as the case of housing in Green Hill Resort City is different from that offered in brochures advertising, misleading advertising brochures such as the case the ad is associated with the principle of absolute responsibility (strict liability) is set in the positive law of Indonesia contained in several articles in Law Number 8 Year 1999 About Legal Protection for consumers of misleading advertisements in the UUPK. Another form to protect consumers, namely the establishment of the National Consumer Protection Agency (BPKN) which is regulated in Chapter VIII UUPK from Article 31 to Article 43. Second, Causes Factors Business Actor Who Make Misleading Consumers In the Housing Brochure First, Lack of Awareness of Perpetrators Attempt to Consumer Rights. Secondly, the existence of business opportunity opportunities to create misleading advertisements there are several factors: Consumer's ignorance of misleading advertising and consumer conditions that lack the courage, knowledge, time and cost to ask for accountability. Third, the Business Lack of Liability for Business Actor. Suggestion Writer is To society as consumer to more firmly to able to fight for rights ownedKeywords: Misleading Advertising - Strict Liability -Residential Responsibility